Effectiveness of combined regional-general anesthesia for reducing mortality in coronary artery bypass: meta-analysis - Barbosa,Fabiano Timbó (2016)
ABSTRACT BACKGROUND AND OBJECTIVES: Neuraxial anesthesia (NA) has been used in association with general anesthesia (GA) for coronary artery bypass; however, anticoagulation during surgery makes us question the viability of benefits by the risk of epidural hematoma. The aim of this study was to perform a meta-analyzes examining the efficacy of NA associated with GA compared to GA alone for coronary artery bypass on mortality reduction. METHODS: Mortality, arrhythmias, cerebrovascular accident (CVA), myocardial infarction (MI), length of hospital stay (LHS), length of ICU stay (ICUS), reoperations, blood transfusion (BT), quality of life, satisfaction degree, and postoperative cognitive dysfunction were analyzed. The weighted mean difference (MD) was estimated for continuous variables, and relative risk (RR) and risk difference (RD) for categorical variables. RESULTS: 17 original articles analyzed. Meta-analysis of mortality (RD = -0.01, 95% CI = -0.03 to 0.01), CVA (RR = 0.79, 95% CI = 0.32-1.95), MI (RR = 0.96, 95% CI = 0.52-1.79) and LHS (MD = -1.94, 95% CI = -3.99 to 0.12) were not statistically significant. Arrhythmia was less frequent with NA (RR = 0.68, 95% CI = 0.50-0.93). ICUS was lower in NA (MD = -2.09, 95% CI = -2.92 to -1.26). CONCLUSION: There was no significant difference in mortality. Combined NA and GA showed lower incidence of arrhythmias and lower ICUS.